Chapter Progressivo e imminentivo nel sistema verbale dell'albanese d'Italia - ALTIMARI, Francesco (Biblioteca di Studi Slavistici, 2023)
This article deals with some specific characteristics of the Italo-Albanian (Arbëresh) verbal system, including the "presumptive" and "unfinished" past, but focuses especially on the expression of Aktionsart with the help of periphrases variously present, if not only marginally, in Balkan Albanian and already attested in the first Arbëresh grammars of the 19th century. The distribution of the periphrastic constructions with progressive and imminentive functions in a series of Italo-Albanian dialects is analysed on the basis of an initial overview of durative periphrases presented in Savoia (1991), but enriched by further research and integrated into a broader typological overview. The author hypothesises that the periphrases in question are not so much the result of linguistic contact with actual Italo-Romance varieties, but rather go back to the Balkan context of possibly Proto-Romance origin.